Mice lacking renal chloride channel, CLC-5, are a model for Dent's disease, a nephrolithiasis disorder associated with defective receptor-mediated endocytosis. - Wang, S; Devuyst, O; Courtoy, P; Wang, X; Wang, H; Wang, Y; Thakker, R; Guggino, S; Guggino, W (2000)
Nephrolithiasis (kidney stones) affects 5-10% of adults and is most commonly associated with hypercalciuria, which may be due to monogenic renal tubular disorders. One such hypercalciuric disorder is Dent's disease, which is characterized by renal proximal tubular defects that include low molecular weight proteinuria, aminoaciduria and glycosuria, together with rickets in some patients. Dent's disease is due to inactivating mutations of the renal-specific voltage-gated chloride channel, CLC-5, which is expressed in the proximal tubule, thick ascending limb and collecting duct. The subcellular localization of CLC-5 to the proximal tubular endosomes has suggested a role in endocytosis, and to facilitate in vivo investigations of CLC-5 in Dent's disease we generated mice lacking CLC-5 by targeted gene disruption. CLC-5-deficient mice developed renal tubular defects which included low molecular weight (<70 kDa) proteinuria, generalized aminoaciduria that was more pronounced for neutral and polar amino acids, and glycosuria. They also developed hypercalciuria and renal calcium deposits and some had deformities of the spine. Furthermore, endocytosis as assessed by horseradish peroxidase uptake in the proximal tubule was severely impaired in CLC-5-deficient mice, thereby demonstrating a role for CLC-5 in endosomal uptake of low molecular weight proteins. Thus, CLC-5-deficient mice provide a model for Dent's disease and this will help in elucidating the function of this chloride channel in endocytosis and renal calcium homeostasis.